Porous Silicon Microparticles for Delivery of siRNA Therapeutics - Shen, Jianliang (J Vis Exp, 2015)
Small interfering RNA (siRNA) can be used to suppress gene expression, thereby providing a new avenue for the treatment of various diseases. However, the successful implementation of siRNA therapy requires the use of delivery platforms that can overcome the major challenges of siRNA delivery, such as enzymatic degradation, low intracellular uptake and lysosomal entrapment. Here, a protocol for the preparation and use of a biocompatible and effective siRNA delivery system is presented. This platform consists of polyethylenimine (PEI) and arginine (Arg)-grafted porous silicon microparticles, which can be loaded with siRNA by performing a simple mixing step. The silicon particles are gradually degraded over time, thereby triggering the formation of Arg-PEI/siRNA nanoparticles. This delivery vehicle provides a means for protecting and internalizing siRNA, without causing cytotoxicity. The major steps of polycation functionalization, particle characterization, and siRNA loading are outlined in detail. In addition, the procedures for determining particle uptake, cytotoxicity, and transfection efficacy are also described.